Relative Importance of Heart Failure Events Compared to Stroke and Bleeding in AF Patients - Ninni, Sandro (J Clin Med, 2021)
Introduction: Incident heart failure (HF), ischemic stroke and systemic embolism (IS/SE), and major bleeding related to anticoagulation therapy are still the most frequent events occurring in patients with atrial fibrillation (AF). The aim of this study was to assess the 3-year incidence, predictors, and related mortality of IS/SE, major bleeding, and HF in a large cohort of AF outpatients. Methods and results: We studied 4973 outpatients with prevalent AF included in the CARDIONOR registry. The mean age was 72.9 ± 11.2 years, 24.1% had diabetes mellitus and 78.9% had anticoagulant therapy at baseline. The mean CHA(2)DS(2)Vasc score was 3.4 ± 1.7. After a median follow-up of 3.2 years (IQR: 2.8 to 3.5), incident HF, IS/SE and major bleeding occurred in 10.5%, 3.3% and 2.1% of patients, respectively. When analyzed as time-dependent variables, IS/SE, major bleeding and hospitalization for decompensated HF were all strongly associated with mortality. The independent predictors of incident HF were age, women, hypertension, diabetes mellitus, coronary artery disease and a previous history of HF. A sensitivity analysis in patients without history of HF at inclusion revealed that incident HF remained the most frequent adverse event, occurring in 5.3% of patients, compared to IS/SE (1.7%) and major bleeding (2.5%). Conclusion: HF is a common residual cardiovascular adverse event occurring in AF outpatients and is associated with a very high mortality. Since modifiable risk factors are associated with incident HF, upstream intensive management of these risk factors would be of interest.